Why are immigrants' incarceration rates so low? Evidence on selective immigration, deterrence, and deportation - Butcher, Kristin F.; Piehl, Anne Morrison 1964- (Working paper series / National Bureau of Economic Research, 2007)
The perception that immigration adversely affects crime rates led to legislation in the 1990s that particularly increased punishment of criminal aliens. In fact, immigrants have much lower institutionalization (incarceration) rates than the native born - on the order of one-fifth the rate of natives. More recently arrived immigrants have the lowest relative incarceration rates, and this difference increased from 1980 to 2000. We examine whether the improvement in immigrants' relative incarceration rates over the last three decades is linked to increased deportation, immigrant self-selection, or deterrence. Our evidence suggests that deportation does not drive the results. Rather, the process of migration selects individuals who either have lower criminal propensities or are more responsive to deterrent effects than the average native. Immigrants who were already in the country reduced their relative institutionalization probability over the decades; and the newly arrived immigrants in the 1980s and 1990s seem to be particularly unlikely to be involved in criminal activity, consistent with increasingly positive selection along this dimension.